2019
DOI: 10.1186/s12960-019-0386-0
|View full text |Cite
|
Sign up to set email alerts
|

Upscaling the pharmacy profession in Lebanon: workforce distribution and key improvement opportunities

Abstract: Background The critical role pharmacists play in the healthcare system necessitates close monitoring of their supply, distribution, and competencies. This is especially relevant considering the global increase in the demand for pharmacists. In Lebanon, the pharmacy profession is facing several challenges related to the unplanned supply of pharmacists. The aim of the study is to analyze the Order of Pharmacists registration database and generate workforce distribution over the last six decades. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 27 publications
1
25
0
Order By: Relevance
“…A good understanding of the dynamics of the health labour market is also a prerequisite; knowing how the participation rates, mobility patterns, aspirations and behaviour of workers will evolve is therefore critical. Certain countries have used this type of information to forecast requirements for skills and competencies in the health and social care workforce (United Kingdom of Great Britain and Northern Ireland), 9 improve the distribution of pharmacists (Lebanon) 10 and assess the planning implications of demographic change in the nursing workforce (Ghana). 11 Countries with a small population face additional challenges as they cannot expect to achieve economies of scale and be totally self-sufficient, for instance in the education of highly specialized health workers.…”
Section: Policy Workforce Planning For Uhcmentioning
confidence: 99%
“…A good understanding of the dynamics of the health labour market is also a prerequisite; knowing how the participation rates, mobility patterns, aspirations and behaviour of workers will evolve is therefore critical. Certain countries have used this type of information to forecast requirements for skills and competencies in the health and social care workforce (United Kingdom of Great Britain and Northern Ireland), 9 improve the distribution of pharmacists (Lebanon) 10 and assess the planning implications of demographic change in the nursing workforce (Ghana). 11 Countries with a small population face additional challenges as they cannot expect to achieve economies of scale and be totally self-sufficient, for instance in the education of highly specialized health workers.…”
Section: Policy Workforce Planning For Uhcmentioning
confidence: 99%
“…On the other hand, pharmacy graduates who studied outside the country can get easily licensed to practice after passing oral and written examinations [4]. A recent study showed that 29% of actively registered pharmacists in Lebanon have studied abroad [7]. Unlike Lebanon, many countries have developed a challenging and long-term process for foreign-trained pharmacists to be integrated in their health care system.…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps more disconcerting, is the absence of a national health human resources forecasting model to advise on the current and future needs for pharmacists in Lebanon [4,7]. This has contributed to the lack of coordination between the educational and practice sectors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations